2021
DOI: 10.3390/ph14010065
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine for the Treatment of Depression: Effects on the Neuroendocrine-Immune Network

Abstract: The neuroimmune and neuroendocrine systems are two critical biological systems in the pathogenesis of depression. Clinical and preclinical studies have demonstrated that the activation of the neuroinflammatory response of the immune system and hyperactivity of the hypothalamus–pituitary–adrenal (HPA) axis of the neuroendocrine system commonly coexist in patients with depression and that these two systems bidirectionally regulate one another through neural, immunological, and humoral intersystem interactions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 226 publications
(230 reference statements)
1
12
0
Order By: Relevance
“…From the perspective of TCM, the model rats not only present the endocrine-immune system disorders caused by the deficiency of yin blood in the liver meridian, but also show changes in the neuroendocrine system disorders caused by the stagnation of liver qi. This is also consistent with the view that the pathogenesis of depression is involved in the neuroendocrine-immune network (41,42). In this paper, pharmacological studies showed that depression-like behavioral deficits in model groups and the lowered or increased levels of the peripheral hemogram, HPA axis, and organ index were ameliorated by AF and PF.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…From the perspective of TCM, the model rats not only present the endocrine-immune system disorders caused by the deficiency of yin blood in the liver meridian, but also show changes in the neuroendocrine system disorders caused by the stagnation of liver qi. This is also consistent with the view that the pathogenesis of depression is involved in the neuroendocrine-immune network (41,42). In this paper, pharmacological studies showed that depression-like behavioral deficits in model groups and the lowered or increased levels of the peripheral hemogram, HPA axis, and organ index were ameliorated by AF and PF.…”
Section: Discussionsupporting
confidence: 90%
“…AF and PF could significantly increase the thymus index and spleen index, improving the abnormal immune function of the body. With increasing bloodbrain barrier permeability, peripheral cytokines can be actively transported into the CNS, subsequently, followed by a reduction in serotonin neurotransmission and the activation of the HPA axis (41). As the hub of the neuroendocrine network, the HPA axis plays an important role in the pathogenesis of depression, with the dysregulation of the HPA axis (48), increasing extracellular glutamate levels and glutamate neurotransmission, and then impacting hippocampal neurogenesis, and through glucocorticoids, the HPA axis is involved in anti-inflammatory, pro-inflammatory and other immune regulatory processes (49).…”
Section: Discussionmentioning
confidence: 99%
“…As a flavonol with numerous biological activities, quercetin has different pharmacological effects such as antidepression, anti-cancer, antioxidant, anti-fibrosis, and antiinflammatory (Reyes-Farias and Carrasco-Pozo, 2019;Ou et al, 2020;Alshammari et al, 2021). Many studies have suggested the protection of mature neurons in the hippocampus, improvement of HPA axis dysfunction, anti-inflammatory, and anti-oxidative stress were involved in the antidepressant effects of quercetin (Sun et al, 2007;Bicca et al, 2021;El-Haroun et al, 2021;Han et al, 2021;Li et al, 2021;Sun et al, 2021), which also encompasses hippocampal neurogenesis promotion through direct and indirect effects (Chan et al, 2018;Rahvar et al, 2018;Wang et al, 2021a;Ma et al, 2021). Hence, quercetin has multiple targets and pathways compared to other antidepressants (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…This paradoxical phenomenon reminds us to be more cautious in future. First of all, as numerous studies in vivo have confirmed that quercetin could act on multiple targets in depression treatment (El-Haroun et al, 2021;Han et al, 2021;Li et al, 2021), the top priority of in vitro studies is not to prove whether quercetin has new targets in treating depression, but to reveal the mechanisms of the proved targets through more scientific models and methods. Besides, based on the difficulties to distinguish the non-specifically and therapeutically irrelevant effects (Baell, 2016), it is necessary to review the false positives and related mechanisms of quercetin, in order to guide researchers to select appropriate cells, culture mediums, control groups and evaluation methods.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, anti-inflammatory drugs like celecoxib could effectively relieve the symptoms of depression ( 94 ). Many herbal medicines are well-documented for anti-inflammatory properties and potential in the treatment of depression in the inflammatory model of depression ( 95 ). Crocus sativus L. (Saffron) is an important medicinal ingredient and also a common spice in North African, Mediterranean, and Middle Eastern countries.…”
Section: Herbal Medicines For the Treatment Of Depressionmentioning
confidence: 99%